ANALISIS KEBUTUHAN PENGEMBANGAN BUKU SAKU BIOLOGI BERBASIS MIND MAP (BIOMAP) - Suryanda, Ade; Azrai, Eka Putri; Julita, Anita (Universitas Tanjungpura, 2020)
Pocketbook based on Mind Map is a supporting book with a size smaller than the standard size, which is systematically in accordance with the working principle of the brain and does not require extensive space in storing it. The aims of studies to explore the potential for developing biology pocketbook based on Mind Map (BIOMAP). This is a descriptive qualitative study with survey methods. The Data collected using the instrument developed that was validated by two experts and tested on 51 students and two high school biology teachers in Jakarta. The results obtained explained that around 72.5% of respondents answered that biological material was difficult to learn. For difficult material, 53.8% of respondents answered Animalia and Plantae. Biological learning difficulties are dominated by the amount of memorization in the material according to the opinion of 72.1% of respondents. Teacher respondents argue that additional learning resources can stimulate students to improve their learning outcomes. The existence of various additional learning resources it is hoped that it can be a solution to the learning problems experienced by students. Based on these data, it can be concluded that students need additional innovative and interesting learning resources accompanied by mind maps. AbstrakBuku saku berbasis Mind Map merupakan buku pendukung berukuran lebih kecil dari buku standar, yang secara sistematis sesuai dengan prinsip kerja otak dan tidak memerlukan ruang luas dalam menyimpannya. Penelitian ini bertujuan untuk mengeksplorasi potensi pengembangan buku saku biologi berdasarkan Mind Map (BIOMAP). Penelitian ini merupakan penelitian kualitatif deskriptif dengan metode survei. Data dikumpulkan menggunakan instrumen yang telah divalidasi oleh dua ahli dan diuji pada 51 siswa dan dua guru biologi SMA di Jakarta. Hasil yang diperoleh menjelaskan bahwa sekitar 72,5% responden menjawab bahwa materi biologi sulit dipelajari. Untuk materi yang sulit, 53,8% responden menjawab materi Animalia dan Plantae. Kesulitan belajar biologi disebabkan banyaknya hafalan pada materi tersebut menurut pendapat 72,1% responden. Responden guru berpendapat bahwa sumber belajar tambahan dapat merangsang siswa untuk meningkatkan hasil belajar mereka. Adanya berbagai sumber belajar tambahan diharapkan dapat menjadi solusi bagi masalah belajar yang dialami siswa. Berdasarkan data ini, dapat disimpulkan bahwa siswa membutuhkan sumber belajar yang inovatif dan menarik yang disertai dengan mind map.Kata kunci: BIOMAP, Buku saku, Mind Map, need assessment